Comparison of K-Means and K-Medoids in Clustering Regency/City in West Sumatra Province Based on Environmental Indicators - Silfi Robiati; Dina Fitria; Dodi Vionanda; Dwi Sulistiowati (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2024)
The Environmental Quality Index is an index that describes the condition of environmental management results nationally, and generalises from all regencies/cities and provinces in Indonesia. Although the Environmental Quality Index of West Sumatra Province has increased, there are still regencies/cities in West Sumatra Province have decreasing Environmental Quality Index. Therefore, it is necessary to conduct further analysis, one of which is to form a group of regencies/cities into a group according to their similarities or characteristics. This study aims to compare the K-Means and K-Medoids methods in grouping regencies/cities in West Sumatra Province based on environmental quality indicators in 2023. The data used in this research is secondary data, which is orginally the publication of Central Bureau of Statistics namely Sumatera Barat Dalam Angka in 2024. The research compares the K-Means cluster method and the K-Medoids cluster method. It concludes K-Means better than K-Medoids methods based on DB index with three clusters. First cluster has 12 regencies/cities with a high average air quality index, the second cluster has 6 regencies/cities that have small amounts of waste, and the third cluster has 1 city with a high average water quality index and land quality index, but a large amount of waste. Keywords: Cluster, Comparison, Environmental, K-Means, K-Medoids